(untitled) (Journal of the College of Basic Education, 2022)
The importance of intertextuality lies in considering it a creative literary context in which the boundaries between the past and the present are abolished in order to renew and develop literature. It is a necessity to link literary work to life through the use of other living texts, whether they belong to a literary or historical work.